2018
DOI: 10.1111/agec.12418
|View full text |Cite
|
Sign up to set email alerts
|

Neighbors follow early adopters under stress: panel data analysis of submergence‐tolerant rice in northern Bangladesh

Abstract: The benefits of a stress-tolerant crop become visible under the stresses that the crop is tolerant against. We investigate the adoption of submergence-tolerant rice in northern Bangladesh by using panel data of 461 households, interviewed in 2013 and 2015. The sample households were randomly selected in 31 villages where submergence-tolerant rice seeds were given to a small number of farmers in each village. The results from the household fixed-effects model indicate that submergence in the previous year incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…They find that the use of this risk-reducing variety leads to higher adoption of other improved agricultural inputs and practices, such as adoption of a more labor-intensive planting, inorganic fertilizer application, and credit utilization. One issue of abiotic stress-tolerant varieties is that the benefits of adoption become visible only when the specific stress, which they are tolerant to, appears (Yamano, Luz, Habib, & Kumar, 2018;Yorobe et al, 2016). The study of submergence-tolerant rice variety adoption in Bangladesh shows that experience of submergence in the previous year increases adoption (Yamano et al, 2018).…”
Section: Adoption Of Improved Varietiesmentioning
confidence: 99%
See 3 more Smart Citations
“…They find that the use of this risk-reducing variety leads to higher adoption of other improved agricultural inputs and practices, such as adoption of a more labor-intensive planting, inorganic fertilizer application, and credit utilization. One issue of abiotic stress-tolerant varieties is that the benefits of adoption become visible only when the specific stress, which they are tolerant to, appears (Yamano, Luz, Habib, & Kumar, 2018;Yorobe et al, 2016). The study of submergence-tolerant rice variety adoption in Bangladesh shows that experience of submergence in the previous year increases adoption (Yamano et al, 2018).…”
Section: Adoption Of Improved Varietiesmentioning
confidence: 99%
“…One issue of abiotic stress-tolerant varieties is that the benefits of adoption become visible only when the specific stress, which they are tolerant to, appears (Yamano, Luz, Habib, & Kumar, 2018;Yorobe et al, 2016). The study of submergence-tolerant rice variety adoption in Bangladesh shows that experience of submergence in the previous year increases adoption (Yamano et al, 2018). In addition, the study of drought-tolerant maize adoption in Malawi demonstrates that previous early season dry spells and access to seed subsidy increase adoption (Katengeza, Holden, & Lunduka, 2019).…”
Section: Adoption Of Improved Varietiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Under normal conditions, farmers observe no additional benefit from submergence-tolerant rice varieties over other popular varieties, these benefits become apparent only after plants are submerged for longer than most varieties can tolerate. A recent study in Bangladesh by Yamano et al (2018) found that the adoption of submergencetolerant rice varieties increased among neighbors of early adopters only after flooding occurred in their area. To encourage farmers to adopt submergencetolerant or other crops with hidden benefits, including nutrition-enhanced crops, campaigns are needed to disseminate this information to farmers.…”
Section: Box Stress-tolerant Crop Varietiesmentioning
confidence: 99%